Penerapan Sistem Informasi Akuntansi Berbasis Teknologi pada Badan Pusat Statistik Kota Palembang - Pelantri, Vivit; Aliya, Sabeli (Ikatan Da'i Indonesia, 2025)
This study aims to determine the application of technology-based accounting information systems. This type of research uses a quantitative descriptive approach with primary data and secondary data types. Data sources were obtained by questionnaires. This study consisted of 30 respondents through sampling techniques using convenience sampling. The results show that it is expected to provide benefits regarding the importance of applying technology-based accounting information systems in supporting more effective accounting processing.